Does Inflation Rate Convergence Spur Exchange Rate Volatility? Empirical Evidence from Sub-Saharan Africa - Mose, Naftaly; Kaboro, Jane (Asian Journal of Economic Modelling, 2019)
Attaining a monetary union is an ambition for most regional economic blocks. However, the arrangement towards monetary union for the East African nations has remained indifferent. The inflation rate is critical for EAC members to achieve a level of harmonization required for establishing a stable and sustainable monetary union. Most existing studies on the relationship show conflicting results and mainly focus on developed countries. It was against this backdrop that the study sought to determine the effect of convergence in the inflation rate, a panel data of 5 countries, for the period 2000-2016 was used. Secondary data was obtained from the Statistical Abstracts and World Bank Report. The study was guided by the Optimum Currency Area framework. The study made use of Standard deviation and LCC to determine convergence and panel unit root respectively. LCC test established that the exchange rate and inflation are stationary at level. Standard deviation test concluded that inflation and exchange rate manifested a negative relationship. This means that convergence in inflation among the EAC countries reduces exchange rate variability within the region. Thus a policy should be made towards controlling this effect resulting from Inflation as East Africa bids for monetary union.